Perancangan Sistem Informasi Akuntansi Penerimaan Kas Berbasis Microsoft Access Pada CV. Royal Mandara: Perancangan Sistem Informasi Akuntansi - Nugraheni Nurwulandari Nugrah; Eka Jumarni Fithri; Yuli Antina Aryani (Jurnal Pengabdian Masyarakat Akuntansi, Bisnis & Ekonomi, 2026)
The development of information technology encourages companies to implement a computerized financial recording system to improve efficiency and accuracy in data management. CV Royal Mandara, a laundry service business in Palembang, still uses a manual system in recording cash receipts which causes potential recording errors, delays in preparing reports, and difficulties in disbursing historical data. This research aims to design a Microsoft Access-based cash receipt accounting information system as a solution to overcome these problems. The data collection method used is observation and direct interviews with business owners. The designed system includes the creation of databases, tables, queries, forms, and reports that produce proof of cash entry, cash receipt reports, and recapitulation reports automatically. The design results show that the new system can improve the accuracy, time efficiency, and reliability of cash receipt data compared to the manual system. This system also supports faster and more precise decision making by management.